Évolution grammaticale et genèse morpho-sémantique de /tôt - Binène Horchani (Multilinguales)
This article will aim to question the uselessness or usefulness of applying in French (both in Spanish and Italian), within the framework of an analysis that is both semantic-morphological and inter/intra-linguistic, the existence of /tôt/ as a morpheme whose transcategorial distribution would include both free uses, mainly adverbial, infralexical uses (bientôt, aussitôt, plutôt tantôt, etc.) and supralexical uses, massively in the form of locutions. It will therefore be a question of asking whether tôt, tantôt, aussitôt, plutôt, etc., (in French), presto (in Italian), and pronto (in Spanish) are semantic units which share the same Latin morpheme / tŏstare / or no.